2016
DOI: 10.1186/s13054-016-1303-8
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and outcome of Middle East respiratory syndrome in Saudi intensive care unit patients

Abstract: BackgroundMiddle East respiratory syndrome coronavirus infection is associated with high mortality rates but limited clinical data have been reported. We describe the clinical features and outcomes of patients admitted to an intensive care unit (ICU) with Middle East respiratory syndrome coronavirus (MERS-CoV) infection.MethodsRetrospective analysis of data from all adult (>18 years old) patients admitted to our 20-bed mixed ICU with Middle East respiratory syndrome coronavirus infection between October 1, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 38 publications
4
74
1
Order By: Relevance
“…They mainly include cough and shortness of breath, as shown by evidence. (10) Up to date, there is no specific treatment or antiviral drugs for MERS-CoV, only supportive treatment is considered for management. (11) During Hajj season, millions of Muslims pilgrim to Makkah city as a part of their religious rituals.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…They mainly include cough and shortness of breath, as shown by evidence. (10) Up to date, there is no specific treatment or antiviral drugs for MERS-CoV, only supportive treatment is considered for management. (11) During Hajj season, millions of Muslims pilgrim to Makkah city as a part of their religious rituals.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Since then, most outbreaks have occurred in KSA. These include a cluster of 25 cases in Al-Hasa between April 1st and May 23rd 2013 (Assiri et al, 2013a), 255 laboratory-confirmed cases in Jeddah between January 1st and May 16th, 2014 (Drosten et al, 2015;Oboho et al, 2015), 45 cases in King Fahad Medical City in Riyadh between March 29th and May 21st, 2014, with contemporaneous outbreaks in other Riyadh hospitals between March and April 2014 (Almekhlafi et al, 2016;Fagbo et al, 2015), and 130 cases at King Abulaziz Medical City in Riyadh during late June-late August 2015 (Balkhy et al, 2016a). An exception was the major outbreak that occurred in in the Republic of Korea between 20 May and 27 July 2015 (Nishiura et al, 2016a,b;Park et al, 2015).…”
Section: Epidemiologymentioning
confidence: 99%
“…Clearly, MERS-CoV is a serious public health issue in KSA. Extended outbreaks of the disease have been focused on healthcare facilities, with transmission apparently dependent on close human-to-human contact (Almekhlafi et al, 2016;Assiri et al, 2013a;Balkhy et al, 2016a;Drosten et al, 2015;Fagbo et al, 2015;Oboho et al, 2015). The emergence of this disease has therefore had a profound impact on infection control and prevention procedures in KSA as outbreaks in healthcare facilities have been associated with defective or inadequate infection prevention and control measures (Balkhy et al, 2016b;Butt et al, 2016;Cotten et al, 2014;Hastings et al, 2016).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The virus was initially isolated from a patient with a fatal community acquired pneumonia (CAP) in Saudi Arabia [1]. Since then, multiple hospital outbreaks occurred within [2][3][4][5][6][7] and outside Saudi Arabia [8][9][10][11]. As of May 1st, 2017, the World Health Organization reported 1952 laboratory-confirmed cases worldwide and at least 693 related deaths [12].…”
Section: Introductionmentioning
confidence: 99%